BUSINESS STUDENTS’ PERCEPTION OF ACADEMIC FRAUD AND FRAUD IN THE WORKPLACE - Adrea Fiolita Vella; Sukartini; Amy Fontanella; Novrina Chandra (Malaysian Journal of Business and Economics (MJBE), 2022)
This study aims to analyze the relationship between the perception of students about academic fraud with job fraud. This research was conducted in the year 2021 on students from the Department of Accounting and Business Administration of Padang State Polytechnic. The results of this study indicated that there was a difference between academic fraud and students’ perceptions regarding fraud at work. This study also found that there was no correlation between students’ academic fraud involvement in college and their perception of job fraud. This showed that students knew and realized that acts of fraud at work were unethical even though they did academic fraud in college. This research could be referred to as input for policymakers, particularly in universities, regarding student academic fraud control.